Fatal Journey : the Final Expedition of Henry Hudson. - Mancall, Peter C. (Basic Books, 2009)
From an acclaimed historian, the tale of Henry Hudson's final voyage in search of the Northwest Passage?and the unsolved mystery surrounding his death.